La diversion comme genre : L’écriture et ses labyrinthes à l’époque élisabéthaine - Sophie Chiari-Lasserre (Revue LISA)
This paper focuses on the notion of “genre(s)” and tries to demonstrate that in the Renaissance England, artists often relied on a labyrinthine genre to improve the subtlety of the writings. The image of the labyrinth was chosen for a variety of reasons: derived from classical sources, sometimes representing chaos, sometimes standing for a complex harmony, this rich, ambivalent figure was at the same time attractive and repulsive. Gradually, the myth pervaded reality: under the Tudors, several kinds of mazes entertained Shakespeare’s compatriots. Indeed, knots and maze gardens proliferated, literally provoking the amazement of people contemplating their twists and turns. The old tradition which consisted in treading the path of a turf-maze still persisted, as Elizabethan literature shows, even though less and less young people wanted to take part in these pagan rituals. In the seventeenth century, poets started lamenting the gradual disappearance of these curves drawn on the grass. Still, the myth of the labyrinth was very pregnant in narrative, dramatic and poetic fictions. With its eccentricities and its extravagances, Renaissance literature gave the symbol a new life. Such translations as Edward Fairfax’s Godfrey of Bulloigne or the Recoverie of Jerusalem (1600) and Robert Dallington’s Hypnerotomachia (1592) allow us to enter a world full of “diversions” – in both senses of the word – and of intricate mazes. And more importantly, the image of the Cretan circumvolutions, when present in the texts, refashioned the style of Renaissance books: this is the reason why the labyrinth itself can be seen as a genre, fully operative during the Elizabethan period. Dramatists in particular used this peculiar genre to stage deviant trajectories and plots of “seduction”, in the etymological sense of the term. More generally, writers re-shaped labyrinthine discourses in order to respect the ideal of copia which had been defended by Erasmus. Finally, this essay explores the multiple meanings of “erring” for the Renaissance artists, given the fact that many of them played on its different facets (going astray or making a wrong choice), in order to produce “amazing”, and sometimes deceiving, literary works.